The relationship between emotional labor and professional burnout: A comparative analysis between work of teachers and employees of commercial service sector - Agnieszka Springer; Karolina Oleksa (Nofer Institute of Occupational Medicine, 2017)
Background: Nowadays more and more employees are required to perform emotional labor (EL) which means that they need to express emotions set by the organizational procedures, simultaneously masking the true feelings. Employees, while performing emotional labor, choose between one of the two strategies (surface acting or deep acting) and this leads to e.g., burnout. As the performance of emotional labor and its consequences depend on the specification of work and chosen strategy, it was assumed that the consequences of EL may be different for workers in various occupations. Material and Methods: The authors performed a comparative analysis between teachers (N = 129) and professionals of commercial service sector (N = 136). In the analysis the Polish adaptation of deep acting and surface acting scale (DASAS) and the Polish version of OLBI (Oldenburg Burnout Inventory) were used. Results: The statistical verification of hypotheses showed that employees of commercial service sector show a greater tendency toward choosing surface acting than teachers. Furthermore, in the group of teachers negative consequences are more related to emotional exhaustion, while both components of burnout are at the same level among employees of the other group. In both groups of respondents surface acting leads to the increase in burnout. Conclusions: Emotional labor can lead to a variety of negative consequences, e.g., burnout or psychosomatic diseases. Based on this knowledge, organizations can develop standards for the expression of emotions and preventive actions, such as identification with organization, which can counteract the negative EL consequences. Med Pr 2017;68(5):605-615